Protective effect and underlying mechanism of muscone on acute cerebral ischemia-reperfusion injury in rats. (23rd May 2023) - Zhang, Pei; You, Suxin; Ding, Xinyue; Luan, Pengwei; Xu, Jiazhen; Cui, Qianfei; Wang, Feiyun; Li, Ruixiang; Zhu, Yuying; Zhang, Jiange
Abstract: Ethnopharmacological relevance: Musk is a widely used traditional Chinese medicine, which has resuscitation, activating blood, and disperse swelling effects. Musk is commonly used in the prevention of myocardial infarction and ischemic stroke, and muscone is its main active component. Aim of the study: The effect and mechanism of muscone to improve the condition of ischemic stroke is not clear, accordingly, we verified its efficacy in ischemia-reperfused rats, and investigated its mechanism by PC12 and THP-1 cells. Methods: A transient middle cerebral artery occlusion (tMCAO) rat model was established for in vivo experiments. 2, 3, 5-Triphenyl Tetrazolium Chloride (TTC) staining was used to calculate infarct rate. Neuroprotection and angiogenesis were assessed by Hematoxylin-eosin (HE) staining, nissl staining, immunofluorescence staining, and quantitative real-time PCR (qRT-PCR). Oxygen glucose deprivation-reperfusion (OGD/R) model of PC12 cells was established for neuroprotection analysis, where CCK-8 assay was used to measure cell viability, flow cytometry and Hoechst 33258 staining were used to demonstrate apoptosis, and protein levels were detected by Western blot. For angiogenesis analysis, enzyme-linked immunosorbent assay (ELISA) and qRT-PCR were used to detect angiogenic factors expressed by THP-1. Cell viability assay, scratch wound assay, and tube formation assay were used to evaluate angiogenic effect of HUVECs treated with medium of THP-1. And the angiogenic pathway in HUVECs was detected by Western blot. Results: According to the results, in cerebral ischemia-reperfusion rats, the infarct rate and tissue damage were significantly reduced by muscone, and the expression of neurotrophic factors and angiogenesis-related factors were all elevated. In OGD/R–PC12 cell models, muscone could increase cell viability and inhibit apoptosis via Bax/Bcl-2/Caspase-3 pathway. In THP-1-mediated angiogenesis of HUVECs, muscone promoted the secretion of angiogenesis-related factors in THP-1 and thus indirectly promoted the proliferation, migration and tube formation of HUVECs, and then regulated phosphorylation of VEGFR2 and Akt in HUVECs. Conclusions: Our study indicated that muscone may be a potential neuroprotective and proangiogenic agent in cerebral ischemia. Graphical abstract: Muscone inhibits neuronal apoptosis induced by acute cerebral ischemia-reperfusion via Bcl-2/Bax/Caspase-3 pathway, and indirectly promotes endothelial cell angiogenesis by activating macrophages, which release angiogenic factors. These neuroprotective and angiogenic effects are beneficial in the recovery from ischemic stroke. Image 1 Highlights: Muscone, a major component of musk, was studied for stroke treatment. Brain injury due to cerebral ischemia is improved by muscone. Muscone inhibits apoptosis induced by oxygen-glucose deprivation. Muscone promotes endothelial cells angiogenesis via macrophages/monocytes.